Viral subversion of nonsense-mediated mRNA decay - Popp, Maximilian Wei-Lin (RNA, 2020)
Viruses have evolved in tandem with the organisms that they infect. Afflictions of the plant and animal kingdoms with viral infections have forced the host organism to evolve new or exploit existing systems to develop the countermeasures needed to offset viral insults. As one example, nonsense-mediated mRNA decay, a cellular quality-control mechanism ensuring the translational fidelity of mRNA transcripts, has been used to restrict virus replication in both plants and animals. In response, viruses have developed a slew of means to disrupt or become insensitive to NMD, providing researchers with potential new reagents that can be used to more fully understand the NMD mechanism.